A Analisis Pemasaran Ikan Katapayi Lande Melalui Platform Digital Marketplace - Yusman Sutoyo (Economics and Digital Business Review, 2023)
Katapayi fish is a great demand by the people of the Buton Islands, but sales are still carried out traditionally. This research aims to analyze the katapayi fish Lande marketing system. The type of research used in this research is descriptive qualitative. The subjects in this research were the Katapayi fish traders in Lande Village, totaling 10 people. The data collection techniques used were sourced from primary and secondary data which was carried out by observation and interviews. Secondary data was obtained from literature searches through literature and articles related to the topic of discussion. The analysis technique used is descriptive analysis, referring to the 4P marketing mix concept (product, price, place, promotion). The results interviews related to the business strategy used by the katapayi fish Lande trader group, in the form of information in narrative form, will be directed to a SWOT analysis which is then applied in its marketing strategy. Katapayi fish Lande products have not had a product brand for a long time, do not have packaging that is vacuumed regularly and do not have a well-planned marketing strategy. Marketing through a digital marketplace platform is the right system for developing the Katapayi Fish business by choosing online services that are quite familiar.